2020
DOI: 10.1039/c9cc09551a
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of sulfonated 4H-3,1-benzoxazines via an electro-chemical radical cascade cyclization

Abstract: We achieved sulfonated 4H-3,1-benzoxazines under ambient conditions without any metals and external chemical oxidants via electrochemical radical cascade cyclizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 75 publications
0
28
0
1
Order By: Relevance
“…80 recently been produced by electrochemical radical cascade cyclisation as reported by He and co-workers. 86 Such a wealth of highly sustainable and green electrosynthetic methods for producing heterocycles from amides provides a very promising foundation for future preparations of valuable pharmaceuticals and agrochemicals, which are largely comprised of heterocyclic compounds.…”
Section: Scheme 49mentioning
confidence: 99%
“…80 recently been produced by electrochemical radical cascade cyclisation as reported by He and co-workers. 86 Such a wealth of highly sustainable and green electrosynthetic methods for producing heterocycles from amides provides a very promising foundation for future preparations of valuable pharmaceuticals and agrochemicals, which are largely comprised of heterocyclic compounds.…”
Section: Scheme 49mentioning
confidence: 99%
“…[275] Electric current was also used as the oxidant for this transformation. [276] Radical traps experiments showed that the reaction proceeded through the generation of sulfonyl radical A from sulfinate anion 523 under oxidative conditions, which was then added to the double bond of o-vinylanilide 522 with the formation of C-centered radical B. The final benzoxazines 524 are formed as a result of subsequent oxidation of radical B into cation C, intramolecular nucleophilic attack, and deprotonation (Scheme 226).…”
Section: Construction Of Six-membered Heterocyclesmentioning
confidence: 99%
“…AgNO 3 ‐ or CAN‐mediated reaction of o ‐vinylanilides 522 with sodium sulfinates 523 under an inert atmosphere led to benzoxazines 524 (Scheme 225). [275] Electric current was also used as the oxidant for this transformation [276] . Radical traps experiments showed that the reaction proceeded through the generation of sulfonyl radical A from sulfinate anion 523 under oxidative conditions, which was then added to the double bond of o ‐vinylanilide 522 with the formation of C‐centered radical B .…”
Section: Sulfonylation Followed By Cyclizationmentioning
confidence: 99%
“…In 2019, the electrochemical radical cascade cyclizations of styrenyl amides with sulfonylhydrazines for the synthesis of sulfonated 4H-3,1-benzoxazines was developed by Huang group. [120] No metal or oxidant was need for this reaction. CV (Cyclic voltammograms) experiments showed that sulfonylhydrazines was oxidized preferentially over styrenyl amides in this electrolysis process.…”
Section: Sulfonylation/cyclization With Alkenesmentioning
confidence: 99%
“…In 2019, the electrochemical radical cascade cyclizations of styrenyl amides with sulfonylhydrazines for the synthesis of sulfonated 4H‐3,1‐benzoxazines was developed by Huang group [120] . No metal or oxidant was need for this reaction.…”
Section: Sulfonylation Reaction Using Sodium Sulfinatesmentioning
confidence: 99%